Korelasi Kemandirian Belajar saat Pandemi Covid-19 terhadap Hasil Belajar Kognitif Peserta Didik Kelas XI pada Mata Pelajaran Sejarah Kebudayaan Islam di MAN 2 Pati - Ainus Sa’adah (Education Mind Based Development Association, 2021)
This research aims to determine: 1) The level of learning independence students of class XI during the Covid-19 pandemic in the SKI at MAN 2 Pati, 2) The cognitive learning outcomes students of class XI during the Covid-19 pandemic in SKI, and 3 ) Is there a positive correlation between independent learning during the Covid-19 pandemic and the cognitive learning outcomes students of class XI in the SKI at MAN 2 Pati. This research design used simple correlation research. The type of research used is quantitative research with a correlation approach. The population of this research were all students in class XI MAN 2 Pati in the academic year 2020/2021 except for class XI IPA 1 and XI IPA 2. The sampling technique used was probability sampling. Some of the instruments used in this research were tests, questionnaires, observation and documentation. Distribution of instruments test and questionnaires to samples via google form. After the research data was collected, it was analyzed using the SPSS program. The results showed that: 1) The level of learning independence students of class XI during the Covid-19 pandemic at MAN 2 Pati was in the medium category with an average learning independence score of 83.99. 2) The cognitive learning outcomes students of class XI at MAN 2 Pati during the Covid-19 pandemic in the SKI subject were in the medium category with the average value of cognitive learning outcomes of students of 54.17. 3) There is a positive correlation between independent learning during the Covid-19 pandemic with the cognitive learning outcomes students of class XI in the SKI at MAN 2 Pati with a sig. (2-tailed) at a 5% error level of 0.022.